The MSHA Strain of Pseudomonas Aeruginosa Activated TLR Pathway and Enhanced HIV-1 DNA Vaccine Immunoreactivity - Hou, Jue; Liu, Yong; Liu, Ying; Shao, Yiming (PLOS ONE, 2012)
The mannose-sensitive hemagglutination pilus strain of Pseudomonas aeruginosa (PA-MSHA) has been shown to trigger naïve immune responses through the activation of monocytes, macrophages, natural killer cells (NK cells) and antigen presenting cells (APCs). Based on the hypothesis that PA-MSHA activates natural immunity through the Toll-like receptor (TLR) pathway, we scanned several critical TLR pathway molecules in mouse splenocytes using high-throughput real-time QRT-PCR and co-stimulatory molecule in bone marrow-derived dendritic cells (BMDCs) following in vitro stimulation by PA-MSHA. PA-MSHA enabled activation of the TLR pathway mediated by NF-κB and JNK signaling in splenocytes, and the co-stimulatory molecule CD86 was up-regulated in BMDCs. We then assessed the adjuvant effect of PA-MSHA for HIV-1 DNA vaccines. In comparison to DNA inoculation alone, co-inoculation with low dosage of PA-MSHA enhanced specific immunoreactivity against HIV-1 Env in both cellular and humoral responses, and promoted antibody avidity maturation. However, high doses of adjuvant resulted in an immunosuppressive effect; a two- or three-inoculation regimen yielded low antibody responses and the two-inoculation regimen exhibited only a slight cellular immunity response. To our knowledge, this is the first report demonstrating the utility of PA-MSHA as an adjuvant to a DNA vaccine. Further research is needed to investigate the exact mechanisms through which PA-MSHA achieves its adjuvant effects on innate immune responses, especially on dendritic cells.